The Effect of Ethical Ideology on Earnings Management Practices - Herman Yosef Sri Widodo (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2020)
Earnings management is taking advantage of the flexibility in the choice of accounting treatment to signal the manager’s private information on future cash flows (Sankar and Subramanyam, 2001). Earnings management can be defined as the practice of using tricks to misrepresent or reduce transparency of the financial reports (Miller and Bahnson, 2002). Ethical ideology consists of the degree of relativism (use of universal moral rules) and idealism (belief that good can come of all situations) exhibited by individuals when they make an ethical decision (Forsyt, 1981). The aim of this research is to examine the influence of ethical ideology on earnings management practices. This study tested hypotheses that Ethical Ideology can influence negatively to the intention of earnings management. For this purpose, the data are collected from 121 students who have already passed Auditing and Business Ethics courses in Accounting Study Program, The Faculty of Business and Economics, Universitas Atma Jaya Yogyakarta. The data was analysed by using SPSS16 version. The result of this research shows that ethical ideology has negative effect on the intention of earnings managementKeywords: earnings management, ethical ideology